Dietetic and nutrition case studies - Lawrence, Judy 1960-; Douglas, Pauline; Gandy, Joan (John Wiley & Sons, 2016)
"The ideal companion resource to Manual of Dietetic Practice, this book takes a problem based learning approach to dietetics and nutrition with cases written and peer reviewed by registered dietitians, drawing on their own experiences and specialist knowledge"--Provided by publisher.